Medical Students Immersed in a Hyper-Realistic Surgical Training Environment Leads to Improved Measures of Emotional Resiliency by Both Hardiness and Emotional Intelligence Evaluation - White, Allana; Zapata, Isain; Lenz, Alissa; Ryznar, Rebecca; Nevins, Natalie; Hoang, Tuan N.; Franciose, Reginald; Safaoui, Marian; Clegg, David; LaPorta, Anthony J. (Frontiers in Psychology, 2020)
Background Burnout is being experienced by medical students, residents, and practicing physicians at significant rates. Higher levels of Hardiness and Emotional Intelligence may protect individuals against burnout symptoms. Previous studies have shown both Hardiness and Emotional IntelIigence protect against detrimental effects of stress and can be adapted through training; however, there is limited research on how training programs affect both simultaneously. Therefore, the objective of this study was to define the association of Hardiness and Emotional Intelligence and their potential improvement through hyper realistic immersion simulation training in military medical students. Methods Participants in this study consisted of 68 second year medical students representing five medical schools who were concurrently enrolled in the United States military scholarship program. During a six day hyper-realistic surgical simulation training course, students rotated through different roles of a medical team and responded to several mass-casualty scenarios. Hardiness and Emotional Intelligence were assessed using the Hardiness Resilience Gauge (HRG) and the Emotional Quotient Inventory (EQ-I 2.0) respectively, at two time points: on arrival (pre-event) and after completion of the course (post-event). Results Hardiness and Emotional Intelligence scores and sub scores consistently improved from pre-event to post-event assessments. No difference in training benefit was observed between genders but differences were observed by age where age was more often associated with Emotional Intelligence. In addition, factor analysis indicated that the HRG and EQ-I 2.0 assessment tools measured predominately different traits although they share some commonalities in some components. Conclusion This study indicates that Hardiness and Emotional Intelligence scores can be improved through immersion training in military medical students. Results from this study support the use of training course interventions and prompt the need for long term evaluation of improvement strategies on mitigating burnout symptoms.